Xanthogranulomatous oophoritis-masquerading as ova-rian neoplasm: report of two cases - Gupta, Neeru; Gupta, Chhaya (Annals of Pathology and Laboratory Medicine, 2015)
Xanthogranulomatous oophritis is an unusual chronic inflammatory condition which clinically presents as a mass like lesion in the pelvic cavity. It invades the surrounding tissue and thus mimics like a tumor. Patients with xanthogranulomatous oophoritis presents with lower abdominal or suprapubic pain, fever, menorrhagia, vaginal bleeding, adnexal tenderness and rarely as a pelvic mass. Only a few cases of this entity have been reported in India. We report two cases of xanthogranulomatous inflammation of the female genital tract presenting with unilateral ovarian masses having clinical and radiological suspicion of an ovarian tumor. Both patients underwent panhystrectomy. Gross examination revealed enlarged unilateral ovaries with multiloculated cystic cavities on cut surface. Histopathological examination revealed massive infiltration of the ovarian tissue by lipid laden histiocytes and mixed inflammatory infiltrate suggesting a diagnosis of xanthogranulomatous oophoritis. These cases mimicked as malignancy and are of interest in view of their rarity.